Diagnostic reference levels for 18F‐FDG whole body PET/CT procedures: Results from a survey of 12 centres in Australia and New Zealand. Issue 3 (15th February 2019) - Alkhybari, Essam M; McEntee, Mark F; Brennan, Patrick C; Willowson, Kathy P; Kench, Peter L
Abstract: Introduction: The aim of this work is to report diagnostic reference levels (DRLs) for hybrid positron emission tomography and x‐ray computed tomography (PET/CT) exams in Australia (AU) for Queensland (QLD) and Western Australia (WA) (AU QLD/WA) and New Zealand (NZ). Methods: Two‐structured booklets were designed to collect dose information, patient demographics, equipment details and acquisition protocols for fluoride‐18 fluorodeoxyglucose ( 18 F‐FDG) PET/CT procedures, and any additional diagnostic CT routinely performed as part of 18 F‐FDG whole‐body examination. The DRL was reported based on the 75 th percentile and achievable dose for 18 F‐FDG, CT dose index volume (CTDIvol ) and dose length product (DLP). The effective dose and total effective dose was reported for 18 F‐FDG whole‐body PET/CT examination. Also, the effective dose was reported separately for identified additional diagnostic CT. Results: The findings of this study show that the current DRL for 18 F‐FDG in AU QLD/WA and NZ was 333.75 MBq and 332.87 MBq, respectively. The reported AU QLD/WA CTDIvol and DLP associated with 18 F‐FDG whole‐body PET/CT examinations from vertex to thigh (VT) was 4.41 mGy and 474 mGy.cm. In NZ, the reported VT CTDIvol and DLP was 13.07 mGy and 1319.05 mGy.cm. The effective dose for 18 F‐FDG and CT component was 5.6 mSv and 4.7 mSv for AU QLD/WA. For NZ, the effective dose was 5.7 mSv and 10.9 mSv for 18 F‐FDG and CT component. The total effective dose delivered from the 18 F‐FDG whole‐body scan from the AU QLD/WA PET/CT centres (10.44 mSv) were lower than the radiation doses delivered from the NZ (16.65 mSv). Conclusions: The current DRLs were proposed for AU QLD/WA and NZ for 18 F‐FDG whole‐body PET/CT examinations. Variations existed in the current practice of AU QLD/WA and NZ PET/CT examinations. There is a need to optimize the radiation doses delivered from PET/CT examinations.